Low-frequency fatigue at maximal and submaximal muscle contractions - Baptista,R.R. (2009)
Skeletal muscle force production following repetitive contractions is preferentially reduced when muscle is evaluated with low-frequency stimulation. This selective impairment in force generation is called low-frequency fatigue (LFF) and could be dependent on the contraction type. The purpose of this study was to compare LFF after concentric and eccentric maximal and submaximal contractions of knee extensor muscles. Ten healthy male subjects (age: 23.6 ± 4.2 years; weight: 73.8 ± 7.7 kg; height: 1.79 ± 0.05 m) executed maximal voluntary contractions that were measured before a fatigue test (pre-exercise), immediately after (after-exercise) and after 1 h of recovery (after-recovery). The fatigue test consisted of 60 maximal (100%) or submaximal (40%) dynamic concentric or eccentric knee extensions at an angular velocity of 60°/s. The isometric torque produced by low- (20 Hz) and high- (100 Hz) frequency stimulation was also measured at these times and the 20:100 Hz ratio was calculated to assess LFF. One-way ANOVA for repeated measures followed by the Newman-Keuls post hoc test was used to determine significant (P < 0.05) differences. LFF was evident after-recovery in all trials except following submaximal eccentric contractions. LFF was not evident after-exercise, regardless of exercise intensity or contraction type. Our results suggest that low-frequency fatigue was evident after submaximal concentric but not submaximal eccentric contractions and was more pronounced after 1-h of recovery.